High Prevalence of ESBL-Producing Klebsiella pneumoniae Causing Community-Onset Infections in China - Zhang, Jing; Zhou, Kai; Zheng, Beiwen; Zhao, Lina; Shen, Ping; Ji, Jinru; Wei, Zeqing; Li, Lanjuan; Zhou, Jianying; Xiao, Yonghong (Frontiers in Microbiology, 2016)
The aim of this work was to investigate the epidemiological and genetic characteristics of ESBL-producing Klebsiella pneumoniae (ESBL-Kp) causing community-onset infections. K. pneumoniae isolates were collected from 31 Chinese secondary hospitals between August 2010 and 2011. Genes encoding ESBL and AmpC beta-lactamases were detected by PCR. The isolates were assigned to sequence types (STs) using multi-locus sequence typing (MLST). Eleven ESBL-Kp strains were selected for whole-genome sequencing (WGS) for investigating the genetic environment and plasmids encoding ESBL genes. A total of 578 K. pneumoniae isolates were collected, and 184 (31.8%) carried ESBL genes. The prevalence of ESBL-Kp varied from different geographical areas of China (10.2–50.3%). The three most prevalent ESBL genes were blaCTX-M-14 (n = 74), blaCTX-M-15 (n = 60), and blaCTX-M-3 (n = 40). MLST assigned 127 CTX-M-14 and CTX-M-15 producers to 54 STs, and CC17 was the most prevalent population (12.6%). STs (23, 37, and 86) that were known frequently associated with hypervirulent K. pneumoniae (hvKP) account for 14.1% (18/127). Phylogenetic analysis by concatenating the seven loci of MLST revealed the existence of ESBL-producing K. quasipneumoniae (two strains) and K. varricola (one strain), which was further confirmed by WGS. This study highlights the challenge of community-onset infections caused by ESBL-Kp in China. The prevalence of STs frequently associating with hvKP should be of concern. Surveillance of ESBL-KP causing community-onset infections now appears imperative.